(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Objective: To study the nature and severity of ethanol related disulfiram reaction Method: Sixty seven male alcoholics otherwise healthy were randomly allocated into low and high dose Disulfiram group. Patients assigned to high dose group were given a cumulative dose of 5gms spread over 4 days. The low dose groups were given a cumulative dose of 2.5gms spread over 7 days. On fourth day in high and seventh day in low dose patients Ethanol challenge was carried out. Details of DER were recorded on a checklist. Severity of DER was measured on a self devised rating scale. Results: Common DER manifestations were flushing, drowsiness, vomiting, fall in blood pressure and raise in pulse rate, in addition both group had some more additional symptoms. Majority of patients developed severe DER in both groups and most of them recovered in about 6 to 8 hrs. Severity of DER was independent of duration of alcohol use, dose of Disulfiram and BMI. Conclusion: The nature and severity of Disulfiram Ethanol Reaction (DER) determines strength of negative reinforcement in deterrent therapy of alcohol dependence. Knowledge of nature of DER helps in following clinical progress of a patient, planning treatment of a patient ingesting alcohol while on Disulfiram and in determining maintenance dose.